Exploring the Neurocognitive Aspects of Creativity and Academic Performance: A Review - Aroutzidis, Anthimos; Antonopoulou, Hera (Technium Education and Humanities, 2024)
This paper investigates the neurocognitive aspect of creativity and academic performance, regarding how these two are interlinked and what implications this has for education. In establishing a theoretical framework, one should be enabled to examine the neurocognitive processes underlying creativity and academic performance: brain structures, neural plasticity, emotional and motivational influences, and environmental stimuli. A systematic review methodology brings into its scope investigations on cortical markers, EEG, and cognitive assessments with respect to the objective evaluation of creativity and academic performance. It includes an overview of the major factors in neurocognitive functioning that influence creativity: working memory, cognitive flexibility, and processing speed; the role of dopamine in creative output; and lastly, the relationship between executive functions and creativity. It presents future neurocognitive interventions, such as cognitive training and mindfulness practices, in improving creativity and academic performance. It therefore calls for integrating neurocognitive research into educational frameworks in a way that optimizes individualized education and calls for interdisciplinary research to bring neuroscience, psychology, and education together in the development of evidence-based educational policies and practices. This should lead to a broad-based analysis and help develop an educational system, neuro-cognitively supportive, for the inclusion of individual differences and closing gaps in cognitive and academic achievement.